ANALYSIS OF FAMILY ISSUES FROM A PSYCHOLOGICAL PERSPECTIVE AS AN EFFORT TO RECONSTRUCT ISLAMIC FAMILY LAW IN INDONESIA - selinah, Selinah; Hairunnas, Hairunnas; Tohirin, Tohirin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study examines the reconstruction of Islamic family law in Indonesia by integrating a family psychology approach to strengthen household resilience and prevent breakdowns caused by early marriage, infidelity, divorce, and domestic violence. From the perspective of fiqh munakahat, the reconstruction of Islamic family law is directed towards redefining marriage norms, including psychosocial maturity requirements, financial responsibility, and the division of parenting roles to achieve justice and compassion within the family. Literature review and policy analysis methods were used to examine the emotional readiness of couples, premarital financial literacy, and sharia-based conflict resolution mechanisms. The results of the study indicate that it is necessary to: (1) revise the Marriage Law to emphasise the integration of psychosocial requirements in Islamic marriage licensing; (2) create a psychosocial-based premarital module that must include training in effective communication, emotion management, and conflict resolution strategies in accordance with the principles of al musawah and al ta‘awun to reduce the risk of divorce; (3) involve family psychologists in premarital counselling at BP4 and religious court mediation to enhance couples' coping abilities; (4) establish effective Family Consultation Institutions (LKK) at the sub-district/village level as interdisciplinary education centres. The implementation of this reconstruction framework is expected to produce proactive, holistic Islamic family law that is oriented towards psychological resilience and the well-being of the community